Creating the National Banana Industry Development Council (a short rhetorical documentary film) - Gasmin, Vincent A.
Following the ?Scarborough Shoal incident? back in the summer of 2012 where our Cavendish Banana exports were closely and strictly monitored by China, there has been a noticeable slump in the Philippine banana industry on multiple levels. This has been an additional blow to the already pestered industry that is being affected by other issues such as plant diseases, issues with revenue generations policies of some LGUs, peace and order situations in the plantation, black propaganda against the banana industry just to name a few. Currently, agencies from both private and public sectors are discussing the appropriate solution to all the pressing challenges and threats that the industry is facing. In response, the researcher proposed a 10-minute short documentary in a rhetorical form to present and tackle the solution the banana industry is looking for to prevent imminent threats, address current issues, and improve the quality and efficiency of the banana trade and its many levels. To establish and support the message of the film, interviews from the agencies that spearheaded the initial Banana Congress in November of 2012 are used to tell the stories from their respective sectors to evoke and call forth action from the people who can make a difference in the industry. In crating this production thesis, the researcher notes that one must be able to establish a concept or idea that meets its goal of persuading the audience wherein the desired outcome is accomplished. In this study, the concept of using stories to gain persuasion as suggested by Walter Fisher is the main objective and is guided by the principles of the Seven-Step Method for Developing a Creative Concept introduced by Friedmann (2006) and Corner?s four modes of visual language and three forms of verbal language in the documentary film form